ANTIOBESITY ACTIVITY OF CASSAVA BIOFLAVONOIDS ON BODY WEIGHT CHANGES AND CARDIOVASCULAR RISK IN SWISS WEBSTER MICE FED BY HIGH-FAT DIET - Rachmani Permana, Athiya
Obesity is abnormal or excessive fat accumulation that poses a risk to health. Obesity is also a risk factor for other diseases, especially cardiovascular disease. The content of bioflavonoids (rutin and nicotiflorin) in cassava leaves is known to have many pharmacological activities, one of which is antiobesity. This study was conducted to prove the antiobesity activity of cassava bioflavonoids (CBDs) and their effect on cardiovascular risk in obesity-induced male Swiss Webster mice. In this study, mice were divided into six groups, namely the normal control group, the obese group, the CBD test group at doses of 100, 200 and 400 mg/kg, and the orlistat group. The antiobesity activity test was divided into 3 phases, namely the acclimatization phase, the induction phase with high-fat diet, and the CBDs testing phase. The anti-obesity activity of CBDs was assessed through the parameters of body weight, food intake, Food Efficiency Ratio (FER), Lee obesity index and fat index. Cardiovascular risk is measured by measuring blood lipid profiles (total cholesterol, High-Density Lipoprotein (HDL), Low-Density Lipoprotein (LDL), triglycerides), Atherogenic Index (AI) and Cardiac Risk Factor (CRF). The results of Lee obesity index and fat index measurements showed that CBDs 200 mg/kg had the lowest average Lee obesity index, epididymal fat index and visceral fat index among the other groups. The results of blood lipid profile measurements showed that the CBDs 200 group had the highest reduction in total cholesterol, LDL and triglycerides on day 14 after administration of sample, respectively, by 40.95%; 62.03%; and 47.65%. The CBDs 400 group increased HDL by 61.05% and decreased LDL by 62.03% after 14 days of administration of sample. Based on the results of AI and CRF calculations, the CBDs 400 group showed the lowest AI and CRF values compared to the other test groups and was statistically significant (p<0.05) compared to the obese group. Thus, CBD 200 mg/kg has been shown to have potential as an anti-obesity agent. A dose of 400 mg/kg is the optimal dose for reducing cardiovascular risk.